Effect of nicotine on rectal mucus and mucosal eicosanoids. Issue 2 (February 1994) - Zijlstra, F J; Srivastava, E D; Rhodes, M; van Dijk, A P; Fogg, F; Samson, H J; Copeman, M; Russell, M A; Feyerabend, C; Williams, G T
Abstract : Because ulcerative colitis is largely a disease of non-smokers and nicotine may have a beneficial effect on the disease, the effect of nicotine on rectal mucosa in rabbits was examined. Nicotine was given subcutaneously by an Alzet mini-pump in doses of 0.5, 1.25, and 2 mg/kg/day for 14 days to three groups of eight animals and compared with eight controls. Mean (SD) serum nicotine concentrations (ng/ml) were 3.5 (1.1), 8.8 (2.3), and 16.2 (5.2) respectively in the treated groups. The thickness of adherent mucus on rectal mucosa in controls (median 36 microns) was significantly reduced by low dose (22 microns, p = 0.0011), and increased by high dose nicotine (48 microns, p = 0.035). Incorporation of radioactive glucosamine into papain resistant glycoconjugates was unchanged, indicating that mucin synthesis was unaltered. Prostaglandins (PG) were reduced, in some cases significantly (6-keto PGF1 alpha, PGF2 alpha, and hydroxy-eicosatetraenoic acid), by nicotine, which showed an inverse dose dependence--with greatest inhibition in relation to the lowest dose. Nicotine, and possibly smoking, may affect colitis by an action on mucosal eicosanoids and on adherent surface mucus secretion in the rectum and large bowel.